2022
DOI: 10.1002/ldr.4239
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rhizosphere soil nitrogen fractions associated with enzyme activities are linked to the microbial community following intercropping combined with nitrogen fertilization

Abstract: Cereal/legume intercropping is effective for reducing chemical fertilizer inputs and achieving sustainable development. However, the effects of intercropping combined with nitrogen (N) fertilization on rhizosphere soil microbial characteristics and N dynamics–enzyme activity relationships remain unclear. A field experiment was performed to analyze rhizosphere soil N fractions, related enzyme activities, and microbial communities on the Chinese Loess Plateau. The results showed that proso millet/mung bean inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In this study, the soil nutrient content increased as the fertilizer application rate increased. At the same time, soil enzymes were crucial active proteins in the soil and played a vital role in maintaining nutrient supply (Liu and Gong 2022). According to this study, the N2P2K2 treatment signi cantly increased the activities of soil UA, APA, CAT, and SA (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, the soil nutrient content increased as the fertilizer application rate increased. At the same time, soil enzymes were crucial active proteins in the soil and played a vital role in maintaining nutrient supply (Liu and Gong 2022). According to this study, the N2P2K2 treatment signi cantly increased the activities of soil UA, APA, CAT, and SA (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Basidiomycota are the key groups in resisting soil rill erosion (Yang et al., 2023). Abundances of the phyla are also significantly associated with rhizosphere soil N fractions (Liu & Gong, 2022). Contents of TN, AN, ammonium N and nitrate N decreased significantly with the large reductions in N input (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Soil enzymes play critical roles in maintaining nutrient availability (Liu & Gong, 2022). This study found that soil enzyme activities were inhibited under salt‐treated conditions, and the activity decrease of PRO and POD were the most apparent.…”
Section: Discussionmentioning
confidence: 99%